Culture teaching in ELT: a study of a culture-based course in undergraduate English programmes in China - Lin, Dai (2018)
This research is designed to investigate the treatment of culture in education policies, teachers’ beliefs and the current practices of culture teaching in undergraduate English programmes in China, with a particular focus on the teaching of the culture-based course A General Survey of English-speaking Countries.